2013
DOI: 10.1186/1743-422x-10-154
|View full text |Cite
|
Sign up to set email alerts
|

The role of indoleamine 2,3-dioxygenase in LP-BM5 murine retroviral disease progression

Abstract: BackgroundIndoleamine 2,3-dioxygenase (IDO) is an immunomodulatory intracellular enzyme involved in tryptophan degradation. IDO is induced during cancer and microbial infections by cytokines, ligation of co-stimulatory molecules and/or activation of pattern recognition receptors, ultimately leading to modulation of the immune response. LP-BM5 murine retroviral infection induces murine AIDS (MAIDS), which is characterized by profound and broad immunosuppression of T- and B-cell responses. Our lab has previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 63 publications
3
25
0
Order By: Relevance
“…Genetic ablation of indoleamine 2,3-deoxygenase (IDO) did not affect MDSCmediated suppression; however, IDO may function in wildtype MDSCs from LP-BM5-infected mice and be compensated for by other mechanisms in the IDO-knockout MDSCs (113). Supporting a potential role for IDO in LP-BM5, overall IDO is increased during MAIDS and may play a role in the associated pain hypersensitivity (65,69,113). Current data are conflicting as to whether increased IDO plays a role in LP-BM5 retrovirus replication and immunodeficiency (65,113).…”
Section: Retrovirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic ablation of indoleamine 2,3-deoxygenase (IDO) did not affect MDSCmediated suppression; however, IDO may function in wildtype MDSCs from LP-BM5-infected mice and be compensated for by other mechanisms in the IDO-knockout MDSCs (113). Supporting a potential role for IDO in LP-BM5, overall IDO is increased during MAIDS and may play a role in the associated pain hypersensitivity (65,69,113). Current data are conflicting as to whether increased IDO plays a role in LP-BM5 retrovirus replication and immunodeficiency (65,113).…”
Section: Retrovirusesmentioning
confidence: 99%
“…Supporting a potential role for IDO in LP-BM5, overall IDO is increased during MAIDS and may play a role in the associated pain hypersensitivity (65,69,113). Current data are conflicting as to whether increased IDO plays a role in LP-BM5 retrovirus replication and immunodeficiency (65,113).…”
Section: Retrovirusesmentioning
confidence: 99%
“…MDSC expansion occurs in several microbial infections including bacterial (Delano et al, 2007;Goñi et al, 2002;Sunderkötter et al, 2004), fungal (Mencacci et al, 2002), parasitic (Giordanengo et al, 2002;Terrazas et al, 2001;Voisin et al, 2004) and viral infections, including, but not limited to, hepatitis B virus (Chen et al, 2011), cytomegalovirus (Daley-Bauer et al,retroviruses: SIV (Sui et al, 2014), HIV (Bowers et al, 2014;Garg & Spector, 2014;Qin et al, 2013;Vollbrecht et al, 2012) and LP-BM5 murine retrovirus (Green et al, 2013). In murine models, MDSCs are identified as CD11b + CD15 2 M-MDSCs, although a phenotypic consensus on these subsets has not been achieved (reviewed, for example, by Talmadge & Gabrilovich, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the few available studies, retrovirus-induced MDSCs frequently display a monocytic phenotype (Garg & Spector, 2014;Green et al, 2013;Qin et al, 2013), in contrast to the granulocytic phenotype more prominently observed in cancer models, and are hypothesized to contribute to in vivo immunosuppression displayed in these retroviral models. Regardless of the disparate MDSC markers used in these studies, retrovirus-induced MDSCs consistently suppress in vitro T-cell responses, utilizing suppressive mechanisms including, but not limited to, nitric oxide (NO) and reactive oxygen species production (Garg & Spector, 2014;Green et al, 2013;Qin et al, 2013;Sui et al, 2014;Vollbrecht et al, 2012). MDSCs contribute to in vitro and ex vivo immunosuppression, but how MDSCs influence retroviral infection in vivo remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…1). The extent of pathogenesis was calculated from established disease parameters, and a disease index was assigned, with disease severity ranging from 0 (no disease) to 5 (most-severe disease) (37)(38)(39). Infected IRF-3 Ϫ/Ϫ mice were almost as resistant as MAIDS-resistant 129 mice, whereas IRF-7 Ϫ/Ϫ mice developed disease equivalent to that seen with the susceptible B6 controls.…”
mentioning
confidence: 99%